Does Metal Matter: Comparing Photophysical Properties of Bis-Cyclometalated Alkynylphosphonium Au(III) and Pt(II) Complexes - Maksim Luginin; Aleksandra Paderina; Anastasia Sizova; Elena Tupikina; Elena Grachova (Molecules)
In this work, two series of Au(III) and Pt(II) alkynylphosphonium complexes of composition [M(CNC)(C2−L−P(CH3)Ph2)]n+ Pt1–Pt3 (n = 0) and Au1–Au3 (n = 1), (CNC = 2,6-diphenylpyridine; L = phenyl, biphenyl, naphthyl) were synthesized and characterized to discover the similarities and differences in photophysical properties between isoelectronic metallocentres. It is shown that Au(III) and Pt(II) complexes obtained demonstrate different photophysical properties despite isoelectronic metal centres, and some reasons for that are discussed based on experimental data and quantum-chemical calculation results. Complex Pt1 also demonstrated the first example of room-temperature solution phosphorescence in the family of [Pt(CNC)(alkynyl)] complexes. It has been found that the crystal packing of Pt1 contains a Pt–H interaction, qualified by quantum-chemical calculations as a unique hydrogen bond.